2021
DOI: 10.1021/acsaem.1c01542
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced CO2 Hydrogenation to Methanol on the Mesostructured Cu–ZnO/Al2O3–ZrO2 Catalyst

Abstract: In order to obtain high catalytic performance of CO 2 hydrogenation to methanol, mesostructured Cu−ZnO/Al 2 O 3 −ZrO 2 (CZAZ) catalysts were prepared, and the microstructure and surface properties were optimized by the weight ratio of Al 2 O 3 and ZrO 2 . Due to the uniform mesoporous structure and strong interaction of Cu with the support, the mesostructured CZAZ-8 catalyst (Al 2 O 3 weight amount in Al 2 O 3 −ZrO 2 was 80%) had a higher active surface area of metallic Cu and more interfaces of Cu and CO 2 ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…1b and c) show that the homogeneous nanoparticles and Cu–ZnO–ZrO 2 have a smaller particle size than Cu–ZnO because of the good dispersion-effect of ZrO 2 . 25,27 The ZnO (0.280 nm), ZrO 2 (0.297 nm), and ambiguous Cu (0.239 nm) lattice spacings can be discerned from Fig. 1d and e.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…1b and c) show that the homogeneous nanoparticles and Cu–ZnO–ZrO 2 have a smaller particle size than Cu–ZnO because of the good dispersion-effect of ZrO 2 . 25,27 The ZnO (0.280 nm), ZrO 2 (0.297 nm), and ambiguous Cu (0.239 nm) lattice spacings can be discerned from Fig. 1d and e.…”
Section: Resultsmentioning
confidence: 94%
“…Table 1 displays that the particle size of ZnO decreases from 28.0 nm to 21.1 nm after compositing the ternary Cu-ZnO-ZrO 2 catalyst, which indicates that the crystallization of ZnO is inhibited by the addition of ZrO 2 . 24,25 The Cu diffraction peaks could not be observed in Fig. 1a due to the lower Cu percentage (1%).…”
Section: Resultsmentioning
confidence: 98%
“…Based on the literatures, ZnO was able to contribute to a moderate basicity due to the Zn−O pair at Cu−ZnO interface [129,195] . As a result, Cu sites were responsible for the reduced basicity and smaller number of basic sites since some basic sites were occupied by Cu and fewer coordinatively unsaturated O 2− ions were present because of the lower net electronic charge [195–198] . To further modify the surface basicity of Cu/ZnO/Al 2 O 3 , the in‐situ formed layered double hydroxides (LDHs) with Al 2 O 3 as both the Al 3+ source and support acted as a precursor, contributing to more medium and strong basic sites after calcination and reduction compared with Al 2 O 3 with only weak basicity [198–200] .…”
Section: Optimization Of Surface Acidity/basicity Of Al2o3‐based Meta...mentioning
confidence: 99%
“…Recently, a large amount of research has been carried out on photocatalytic CO 2 reduction, demonstrating the importance of this subject. As a result of the hydrogenation process of CO 2 to methanol with the optimized surface properties of Cu–ZnO/Al 2 O 3 –ZrO 2 (CZAZ) catalysts, the catalytic performance of CZAZ catalysts with a mesostructure was evaluated. At 513 K and 5 MPa, 8.7 mmol·gcat –1 ·h –1 methanol (STY MeOH ) was obtained over CZAZ . The photocatalytic activity of CO 2 reduction by SnS/(CH 3 NH 3 ) 2 AgBiI 6 (SCABI) has shown that the charge transfer in SCABI follows the Z-scheme band alignment, conducive to the separation of photoexcited electrons and holes, and that electrons accumulating on the CB of the SnS monolayer have the ability to reduce CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…At 513 K and 5 MPa, 8.7 mmol•gcat −1 •h −1 methanol (STY MeOH ) was obtained over CZAZ. 47 The photocatalytic activity of CO 2 reduction by SnS/(CH 3 NH 3 ) 2 AgBiI 6 (SCABI) has shown that the charge transfer in SCABI follows the Z-scheme band alignment, conducive to the separation of photoexcited electrons and holes, and that electrons accumulating on the CB of the SnS monolayer have the ability to reduce CO 2 . Based on the obtained results, the Z-scheme of the SCABI heterostructure proves to be a promising photocatalyst for CO 2 reduction.…”
Section: Introductionmentioning
confidence: 99%